Cholinesterase Inhibition Activity, Alkaloid Profiling and Molecular Docking of Chilean Rhodophiala (Amaryllidaceae) (2018)
ABSTRACT: Amaryllidaceae plants are the commercial source of galanthamine, an alkaloid approved for the clinical treatment of Alzheimer’s disease. The chemistry and bioactivity of Chilean representatives of Rhodophiala genus from the family of Amaryllidaceae have not been widely studied so far. Ten collections of five different Chilean Rhodophiala were analyzed in vitro for activity against enzymes such as acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) as well as for their alkaloid composition by GC-MS. To obtain an insight into the potential AChE and BuChE inhibitory activity of the alkaloids identified in the most active samples, docking experiments were carried out. Although galanthamine was found neither in aerial parts nor in bulbs of R. splendens, these plant materials were the most active inhibitors of AChE (IC50: 5.78 and 3.62 µg/mL, respectively) and BuChE (IC50: 16.26 and 14.37 µg/mL, respectively). Some 37 known alkaloids and 40 still unidentified compounds were detected in the samples, suggesting high potential in the Chilean Amaryllidaceae plants as sources of both novel bioactive agents and new alkaloids.